Pengaruh Keadilan Distributif Penilaian Kinerja, Kepuasan Kerja dan Komitmen Organisasional terhadap Kinerja Karyawan PT Shoetown Ligung Indonesia - Astri Julianari Nurhasanah (Jurnal Syntax Admiration, 2024)
Employee performance is an important aspect of HRM that reflects how effectively employees achieve the responsibilities and tasks assigned by the company, the role of HR is needed to maintain employee performance levels in order to achieve company targets. This study aims to determine the partial effect of distributive justice performance appraisal, job satisfaction and organizational commitment on employee performance at PT Shoetown Ligung Indonesia. This research uses descriptive verification research through interview, survey and questionnaire methods as data collection instruments. The sampling technique of this research is Non Probability Sampling with Systematic Sampling method multiples of 5 (five) with a total of 104 respondents from the total population of 520 employees. Data analysis was done using simple and multiple regression techniques to assess the effect of the independent variable on the dependent variable with the SPSS 26.00 version application. The results showed that partially distributive justice performance appraisal, job satisfaction and organizational commitment have a significant affected on employee performance at PT Shoetown Ligung Indonesia.